1996
DOI: 10.1111/j.1476-5381.1996.tb15539.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CCK receptor antagonists on the antinociceptive, reinforcing and gut motility properties of morphine

Abstract: 1 The ability of a selective CCKA receptor antagonist PD 140548 and a selective CCKB receptor antagonist CI-988 (formerly PD 134308) to modulate the various in vivo properties of morphine was investigated in the rat. 2 PD 140548 dose-dependently (0.001 -1.0 mg kg-1, i.p.) antagonised the development of conditioned place preference to morphine (2.0 mg kg'-, s.c.). In contrast, CI-988 (0.01 -1.0 mg kg-', i.p.) did not affect this morphine-induced behaviour. Neither of the CCK receptor antagonists blocked or gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
0
17
1
Order By: Relevance
“…Blockade of the action of CCK, especial CCK B receptor, potentiates morphine-induced antinociception (Singh et al, 1996;McNally, 1999). However, our result clearly demonstrated that CCK was not involved in the EM-2-induced antianalgesia, which was evidenced by our finding that the pretreatment of antiserum against CCK could not restore morphine-induced antinociception.…”
Section: Em-2 At Subantinociceptive Doses Produces Antianalgesia Agaicontrasting
confidence: 55%
“…Blockade of the action of CCK, especial CCK B receptor, potentiates morphine-induced antinociception (Singh et al, 1996;McNally, 1999). However, our result clearly demonstrated that CCK was not involved in the EM-2-induced antianalgesia, which was evidenced by our finding that the pretreatment of antiserum against CCK could not restore morphine-induced antinociception.…”
Section: Em-2 At Subantinociceptive Doses Produces Antianalgesia Agaicontrasting
confidence: 55%
“…Animals were starved from food for 18 h prior to experiment, but were allowed free access to water. After 80 min of CS-HexFr or normal saline (SAL) administration, 2 ml of a 10% charcoal slurry in 5% powdered gum acacia was administered to each pigeon orally (Singh et al, 1996). For antagonism, MCP (30 mg/kg) or carbachol (0.1 mg/kg) was administered intramuscularly 5 min before drug administration.…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…Indeed, numerous studies have demonstrated that the coadministration of CCK antagonists with morphine prevents the development of antinociceptive tolerance [162,180,181] . Furthermore, behavioral signs of already established antinociceptive tolerance to morphine have been reversed by CCK antiserum or CCKB antagonists at doses that did not enhance morphine antinociception in naive rats [167,[182][183][184] . Thus, these studies indicate that CCK has a pivotal role in mediating antinociceptive tolerance to opioids.…”
Section: Role Of Cck As An Endogenous Pronociceptive (Or 'Anti-opioidmentioning
confidence: 99%